A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil - de Sousa, Deise J. Dos Anjos; Silva-Oliveira, Cárlison; Canto, André Luiz C.; Ribeiro, Frank Raynner V. (Zootaxa, 2020)
A new species of Knodus is described from the rio Cupari drainage, a tributary from the right margin of the lower rio Tapajós, Pará State, Brazil. The new species differs from its congeners, except K. geryi, by having a dark basal blotch on each caudal fin lobe (vs. caudal fin lobes with sparse chromatophores, lacking basal blotches) and, with the exception of K. borki, K. heteresthes, and K. pasco, by having 10–12 scales around the caudal peduncle (vs. 13–15).